Family Gathering at the Watkins' Home - Watkins, Howard::::::::: (1986)
Albert Watkins, Adam Watkins, Robin Watkins and Christine Watkins; Back: Rose O'Reilly, Frances Kamp, Howard Watkins and his cousins from Israel Deena Eitan and Yaacov Leor New landscape planted by house; front steps painted red